Factors affecting the performance of delivery centre - Banu, Morsheda; Hashima-E-Nasreen; Nahar, Shamsun (BRAC Research and Evaluation Division (RED), 2019)
The study aimed to measure the performance of delivery centres (DC) and explore the factors related to performance of DCs. Data were collected using qualitative methods during December 2009 - January 2010 from six DCs in the slums of Dhaka city. Findings reveal that the DCs at Magbazar and Kamrangir Char performed 'well' due to availability of community health workers (CHW) , their emotional support and caring attitude, regular antenatal care (ANC) visits, convenient location, cleanliness and free services of the DCs. The DCs at Madertek and Shyampur performed 'average' and Ramna and Kotwali DCs performed poor. Poor performance was largely due to lack of CHWs, less motivation, frequent dropout due to low remuneration, and recurrent slum demolition. As women reported, the reasons for not attending DCs was fear of being referred to the hospital which might compel them to have a caesarean delivery, lack of comprehensive services at DCs including doctor-assisted normal deliveries, medicines, and emergency case management. Neonatal mortality rate in poor performed DCs found to be high. The respondents suggested that instead of referring women for minor complications, DCs should be competent of providing supervised skilled service package with basic treatment during childbirth, tetanus toxoid during ANC and child immunizations and postnatal care.